Innovative STEM-based Teaching of ‘Power Transmission Systems’ for Electrical Engineering Students - Doan, Van Hai; Le, Huy Tung (International Journal of STEM Education for Sustainability, 2025)
STEM stands for Science, Technology, Engineering and Mathematics. STEM education is an educational method that integrates these fields in an interdisciplinary and hands-on approach, helping students develop critical thinking, problem solving, teamwork and communication skills. STEM education is increasingly asserting its important role in training high-quality human resources to meet the requirements of the 4.0 Industrial Revolution. Implementing the STEM education model at universities is a necessary step to improve training quality and create generations of creative and innovative students. During the process of training students in electrical engineering, in order to achieve high quality and effective training, we boldly researched a new university teaching model: STEM combining experiential pedagogy with the topic of Systems. power transmission system, then guide students to practice operating the power system on the school's practice model. The power transmission system is a complex network of electrical lines, transformer stations and other equipment responsible for transmitting electricity from the place of production (power plant) to the place of consumption (industrial park)… , manufacturing plant, ...). This system plays an important role in ensuring safe, stable and effective electricity supply for all activities of social life.